2016
DOI: 10.1002/jcla.22088
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PCT and urinary β2-MG enhances the accuracy for localization diagnosing pediatric urinary tract infection

Abstract: Objective: The purpose of this article was to investigate whether the combination of urinary beta 2 microglobulin (urinary β 2 -MG) and procalcitonin (PCT) diagnosis could enhance the localization diagnostic precision of pediatric urinary tract infection comparing with single diagnosis. Methods:A study was conducted in the Nephrology Department of Wuhan women and children's health care centre. This study incorporated 85 participants, including 35 children who were diagnosed as upper urinary tract infection (UU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…As urinary β 2 M level is an important reflection of tubular function of the kidneys, measuring the urine level has been used in the localization of UTI in children. Studies have shown that children with upper UTI tend to have higher urinary β 2 M excretion compared to children with lower UTI ( 186 , 187 ) hence allowing for more accurate localization of infection and treatment strategies. Serum and urinary β 2 M have also been shown to be elevated in children with reflux nephropathy ( 188 ).…”
Section: Urinary β 2 M For the Assessment Of Tubulmentioning
confidence: 99%
“…As urinary β 2 M level is an important reflection of tubular function of the kidneys, measuring the urine level has been used in the localization of UTI in children. Studies have shown that children with upper UTI tend to have higher urinary β 2 M excretion compared to children with lower UTI ( 186 , 187 ) hence allowing for more accurate localization of infection and treatment strategies. Serum and urinary β 2 M have also been shown to be elevated in children with reflux nephropathy ( 188 ).…”
Section: Urinary β 2 M For the Assessment Of Tubulmentioning
confidence: 99%
“…and Jung et al . [ 25 , 26 ], the patient (participant 11) who developed an infection following TTPB had higher uB 2 MG concentrations compared with the average group response (Fig. 8 ).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported that patients with UTI express increased concentration of uB 2 MG, and it has been suggested to be helpful in differential diagnosis and early detection of UTI [ 25 , 26 ]. In agreement with previous reports [ 26 , 27 ], our data follow a similar pattern of increased concentration following TTPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endotoxin produced by bacteria and the cytokines secreted during inflammatory reactions are the main reasons for the elevation of PCT. [ 12 , 13 ] Generally, the level of PCT does no elevate, or only slightly increases during virus infection. [ 14 , 15 ] The increase of PCT in the MODS group indicated a possible secondary bacterial infection that could be neglected due to similar respiratory symptom that eventually increased the mortality rate.…”
Section: Discussionmentioning
confidence: 99%